Design, synthesis and structure-activity relationships of 3,5-diaryl-1H-pyrazoles as inhibitors of arylamine N-acetyltransferase. - Fullam, E; Talbot, J; Abuhammed, A; Westwood, I; Davies, S; Russell, A; Sim, E (2013)
The synthesis and inhibitory potencies of a novel series of 3,5-diaryl-1H-pyrazoles as specific inhibitors of prokaryotic arylamine N-acetyltransferase enzymes is described. The series is based on hit compound 1 3,5-diaryl-1H-pyrazole identified from a high-throughout screen that has been carried out previously and found to inhibit the growth of Mycobacterium tuberculosis.